2007
DOI: 10.1227/01.neu.0000303188.72425.24
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Shunt-Dependent Hydrocephalus After Occlusion of Ruptured Intracranial Aneurysms by Surgical Clipping or Endovascular Coiling

Abstract: Clipping of a ruptured aneurysm may be associated with a lower risk for developing shunt dependency, possibly by clot removal. This might influence long-term outcome and surgical decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
76
2
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(91 citation statements)
references
References 44 publications
6
76
2
7
Order By: Relevance
“…Whether or not incidence of SDHC differs significantly between surgical clipping and endovascular coiling is currently unknown. However, several authors have reported results that demonstrated fewer occurrences of SDHC in the surgical treatment group [3][4][5]19) Another study revealed no difference between the two groups 8) . Early evacuation of cisternal clots during surgery is a possible mechanism for lowering SDHC in the surgical group 8) ; however, this is hypothesized only under thick hemorrhagic conditions.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Whether or not incidence of SDHC differs significantly between surgical clipping and endovascular coiling is currently unknown. However, several authors have reported results that demonstrated fewer occurrences of SDHC in the surgical treatment group [3][4][5]19) Another study revealed no difference between the two groups 8) . Early evacuation of cisternal clots during surgery is a possible mechanism for lowering SDHC in the surgical group 8) ; however, this is hypothesized only under thick hemorrhagic conditions.…”
Section: Introductionmentioning
confidence: 97%
“…Suggested risk factors for development of shunt dependent hydrocephalus (SDHC) include location of the aneurysm, Fisher grade (FG) on computed tomography (CT) scan, intraventricular hemorrhage (IVH), and so on 7,13,15,17,20) . Similar to vasospasm, development of hydrocephalus has a strong association with the amount of blood spilled into the subarachnoid space and ventricular system [3][4][5]8) .…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of sNPH has been reported to be 8.9%-48% in patients with SAH. [1][2][3][4][5][6][7]11,12,16,18,22,23 Acute hydrocephalus coexisting with SAH is known to be one of the most important predictors for sNPH. [3][4][5][6]11,16 Previous studies have shown that severe symptoms at SAH onset and a large amount of subarachnoid blood seen on admission CT images are associated with the development of sNPH.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7]11,12,16,18,22,23 Acute hydrocephalus coexisting with SAH is known to be one of the most important predictors for sNPH. [3][4][5][6]11,16 Previous studies have shown that severe symptoms at SAH onset and a large amount of subarachnoid blood seen on admission CT images are associated with the development of sNPH. [3][4][5][6][7][8][9][10][11]12,16,18,23 A posterior circulation location of the ruptured aneurysm and endovascular coil embolization have been reported to be significantly associated with sNPH.…”
mentioning
confidence: 99%
“…After aneurysmal SAH, ventriculoperitoneal shunt dependence due to hydrocephalus is a frequent observation with an incidence up to almost 20% (de Oliveira et al, 2007). Most patients require shunt treatment for malabsorbtive hydrocephalus, although some patients with aneurysms suffer from hydrocephalus due to CSF pathway obstruction rather than malresorption.…”
Section: Surgical Treatmentmentioning
confidence: 99%